Determination of Volatile Organic Compounds in Andean Tomato Landraces by Headspace Solid Phase Microextraction-Gas Chromatography-Mass Spectrometry - Cortina, Pablo Ramiro (2016)
Traditional tomatoes (Solanum lycopersicum L.) have been mainly selected for their fruit quality and maintained by local farmers in Andean areas of Cuyo and Northwestern Argentina. Volatile organic compounds (VOCs) in mature fruits of Andean tomato landraces were evaluated for the first time using headspace solid phase microextraction (HS-SPME) and gas chromatographymass spectrometry (GC-MS) and combined with classical multivariate analysis. The data sets composed of 101 volatile metabolites were identiﬁed in 4 accessions of Andean landraces, one commercial variety and one wild tomato accession (Solanum pimpinellifolium L.). The metabolic profile showed typical VOCs of tomato and 21 new compounds never informed in S. lycopersicum. Andean traditional tomatoes have been shown to be metabolically different from wild species. In addition, some varieties of Andean tomatoes have a different profile of VOCs and are richer than the commercial variety. A different and original metabolic volatile composition found in fruits of Andean tomato landraces of Argentina, in comparison with commercial cultivars, might probably reveals selection based on quality attributes made by local farmers.